Genetics and"democracy" - Federico Marchetti; Giovanni Corsello (BMC, 2022)
Abstract Background The spread of knowledge on the important implications of a diagnosis of genetic disease does not correspond to a sharing of the knowledge and equal rights of children. Main body It is estimated that about 5% of newborns may have a rare disease that in some cases, if diagnosed early, could have specific treatments that may be able to modify the natural history of the disease. However, in most countries the diagnosis during the first hours of life is limited to a few diseases, due to the high costs and time required for genetic investigations with classical methods. Recently, experimental projects to subject all newborns to a complete DNA analysis, with Next Generation Sequencing techniques, to detect any genetic pathologies as early as possible, have been reported in some countries. The late diagnosis of some genetic diseases that have treatment plans, such as spinal muscular atrophy, can be a serious damage, for anyone who has seen and accompanied the life of a child with this disease and his/her family, before and after, the recent availability of therapies which, if started very early, can lead to an almost normal life. Rapid sequencing and genetic diagnosis are a crucial part of directing inpatient management and this resource should be accessible not only to academic medical centers but also in community settings. Conclusions It is time for a profound reflection that places in Italy, as in other countries, the use of genetic tests in neonatal and pediatric age based on principles of evidence, ethics, and democracy and on clear national guidelines, which also consider organizational aspects.